Literary Journalism as Counter-Narrative in Pesantren Reporting on Kediripedia.com - Lukman Hakim; Siti Aminah (DAWUH : Islamic Communication Journal, 2026)
The development of digital media has driven a shift towards fast-paced, efficient journalistic practices, resulting in a proliferation of digital coverage that prioritizes speed and controversy, particularly regarding pesantren (Indonesian Islamic boarding schools). Through literary journalism, Kediripedia.com serves as an alternative media platform that presents information about pesantren from a different perspective, drawing on lived experience. Therefore, this study aims to analyze the implementation of literary journalism in reporting on pesantren on the online media platform Kediripedia.com, using a qualitative approach based on Teun A. van Dijk’s critical discourse analysis model. The data collection techniques employed were interviews with the Managing Editor and Journalists of Kediripedia.com, as well as a documentary study of four news articles on the theme of pesantren, selected via purposive sampling based on the characteristics of literary journalism. The analysis was conducted across three textual dimensions: text structure (macro, superstructure, and micro), social cognition, and social context. The results of this study indicate that Kediripedia.com employs literary journalism through metaphors, emotive vocabulary, third-person pronouns, and dramatic narrative flow. Consequently, the texts are dominated by a narrative writing style. In terms of social cognition, the journalists’ position utilizes a schema comprising events, the self, persons, and roles. In the social context, Kediripedia.com’s news reinforces the local identity of pesantren amidst negative coverage by employing a narrative, emotional, and dramatic writing style.